WATCH OUT FOR BABY-FACED CON. (Architects' Journal, 2005)
Focuses on the latest hacking technique used by computer hackers using the Yahoo sign-in pages such as the Yahoo Photos. Common purpose of the computer hackers in hacking; Risks of hacking; Procedure of the hacking technique using the Yahoo sign-in page Yahoo Photos.